2012
DOI: 10.1108/14717791211231193
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists' attitudes towards old and young patients in persistent vegetative state (PVS)

Abstract: PurposeThe purpose of this paper is to uncover attitudes of physical therapists (PTs) who treat vegetative state (VS) patients, and to raise awareness to ethical and professional dilemmas: Are PTs influenced by ageist perceptions? Do they consider physiotherapy to be effective or futile?Design/methodology/approachEthical questions and complex dilemmas are by and large subconscious and rarely explicitly voiced, but can be identified by revealing implicit therapists' personal and professional approach to patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
0
3
0
1
Order By: Relevance
“…Üniversitelerin tıp fakülteleri dışında hemşirelik, diş hekimliği, eczacılık, fizyoterapi ve rehabilitasyon, ev ekonomisi, beslenme ve diyetetik, sosyal hizmetler, psikoloji, mimarlık ve çevre tasarımı gibi bölümlerinde de yaşlı sağlığı ile ilgili-bağlantılı çalışmalar yürütülmektedir. [8][9][10][11] Literatürde yaşlıya yönelik tutumların olumsuz olmasının meslek yaşamında yaşlıyı ihmal etme ya da olumsuz yönde yaşlı ayrımcılığına yol açabileceği vurgulanmaktadır. 12,13 Özellikle uğraş alanı insan olan sağlıkla ilgili mesleklerde yaşlıya yönelik tutum mesleki pratiğe yansımaktadır.…”
Section: Introductionunclassified
“…Üniversitelerin tıp fakülteleri dışında hemşirelik, diş hekimliği, eczacılık, fizyoterapi ve rehabilitasyon, ev ekonomisi, beslenme ve diyetetik, sosyal hizmetler, psikoloji, mimarlık ve çevre tasarımı gibi bölümlerinde de yaşlı sağlığı ile ilgili-bağlantılı çalışmalar yürütülmektedir. [8][9][10][11] Literatürde yaşlıya yönelik tutumların olumsuz olmasının meslek yaşamında yaşlıyı ihmal etme ya da olumsuz yönde yaşlı ayrımcılığına yol açabileceği vurgulanmaktadır. 12,13 Özellikle uğraş alanı insan olan sağlıkla ilgili mesleklerde yaşlıya yönelik tutum mesleki pratiğe yansımaktadır.…”
Section: Introductionunclassified
“…For example, in access to HIV antiretroviral treatment and heart transplant [ 127 ], and in terms of waiting lists [ 126 ]. There is also a significant preference for treating younger versus older patients in the vegetative state [ 43 ], and a perception that younger people deserve more psychosocial support [ 161 ]. The perceptions of social workers towards homeless people are also less harsh if the target is younger [ 162 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies looked at the influence or rater’s age on the preference for or stereotyping of targets of various ages [ 48 , 64 , 66 , 67 , 69 ], showing inconsistent results. Other studies explored the influence of this determinant in performance evaluations of targets of different ages by either employers [ 30 ] or clients [ 53 , 65 ] or in treatment decisions for younger and older patients [ 43 ]. These studies generally found no or minimal effect of rater age.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, while the challenges of both defining and explaining ageism continue, yet another growing body of research has been conducted into the ways in which ageism manifests itself in everyday life. Indeed numerous studies in the field of healthcare have shown how physicians, nurses, physiotherapists and more, not only hold ageist attitudes towards older patients, but also operate in discriminatory ways, providing older patients with inappropriate care (Inbar et al, 2012;Topaz and Doron, 2013).…”
Section: Ageismmentioning
confidence: 99%